Foods Consumed by US Adults From Cafeterias and Vending Machines: NHANES 2005 to 2014. Issue 5 (June 2019) - Onufrak, Stephen J.; Zaganjor, Hatidza; Moore, Latetia V.; Hamner, Heather C.; Kimmons, Joel E.; Maynard, Leah M.; Harris, Diane
Purpose: As part of wellness efforts, employers may seek to improve the nutritional quality of foods offered and consumed in cafeterias and vending machines. However, little is known about who consumes food from these venues and the types and dietary quality of the foods consumed. Design: Cross-sectional. Setting: Nonschool cafeterias and vending machines. Participants: US adults ≥20 years old. Measures: Prevalence of consuming foods, most common foods eaten, leading calorie sources, 2010 Healthy Eating Index Analysis: Using 24-hour dietary recall data from NHANES 2005-2014 (N = 25, 549 adults), we estimated the prevalence of consuming foods, assessed the most commonly consumed foods, and calculated dietary quality of foods. Results: On a given day, 3.1% of adults consumed foods from cafeterias and 3.9% from vending machines. Consumers averaged 692 kcal from cafeterias and 264 kcal from vending machines. Cafeteria consumers had higher income and education, while vending consumers were more likely to be male and younger adults. Common cafeteria foods included vegetables and fruits, but cafeteria foods were generally high in sodium and low in whole grains. Sugar-sweetened beverages and candies accounted for approximately half of all vending calories. Conclusion: Foods chosen from cafeterias and vending machines do not align well with the Dietary Guidelines for Americans. Improving the dietary quality of foods consumed from these venues could impact millions of adults.